Vitamin B12 status and rate of brain volume loss in community-dwelling elderly. - Vogiatzoglou, A; Refsum, H; Johnston, C; Smith, S; Bradley, K; De Jager, C; Budge, M; Smith, A (2008)
OBJECTIVES: To investigate the relationship between markers of vitamin B(12) status and brain volume loss per year over a 5-year period in an elderly population. METHODS: A prospective study of 107 community-dwelling volunteers aged 61 to 87 years without cognitive impairment at enrollment. Volunteers were assessed yearly by clinical examination, MRI scans, and cognitive tests. Blood was collected at baseline for measurement of plasma vitamin B(12), transcobalamin (TC), holotranscobalamin (holoTC), methylmalonic acid (MMA), total homocysteine (tHcy), and serum folate. RESULTS: The decrease in brain volume was greater among those with lower vitamin B(12) and holoTC levels and higher plasma tHcy and MMA levels at baseline. Linear regression analysis showed that associations with vitamin B(12) and holoTC remained significant after adjustment for age, sex, creatinine, education, initial brain volume, cognitive test scores, systolic blood pressure, ApoE epsilon4 status, tHcy, and folate. Using the upper (for the vitamins) or lower tertile (for the metabolites) as reference in logistic regression analysis and adjusting for the above covariates, vitamin B(12) in the bottom tertile (<308 pmol/L) was associated with increased rate of brain volume loss (odds ratio 6.17, 95% CI 1.25-30.47). The association was similar for low levels of holoTC (<54 pmol/L) (odds ratio 5.99, 95% CI 1.21-29.81) and for low TC saturation. High levels of MMA or tHcy or low levels of folate were not associated with brain volume loss. CONCLUSION: Low vitamin B(12) status should be further investigated as a modifiable cause of brain atrophy and of likely subsequent cognitive impairment in the elderly.